Perception of the Lexeme 'Europe' by Students: A Psycholinguistic Analysis - Postolova, Iryna; Tomarieva, Nataliia (East European Journal of Psycholinguistics, 2018)
The article analyzes the results of the free associative experiment, which was conducted among first-year students during 2016-2018. According to the frequency of reactions, the authors model the structure of the associative field: nucleus, body and periphery; define the morphological and semantic groups of associations on the word-stimulus ‘Europe’ obtained during the experiment, analyze the syntagmatic and paradigmatic relationships among the reactions, build the structure of the resulting associative field. The responses of respondents are significantly dominated by nouns; occasionally occur adjectives, verbs, adverbs and pronouns; adjectives and adverbs are mostly colored with emotions and estimations. Phrases make a significant group of associations phrases (about one fifth). Among the above mentioned things, toponyms and surnames of well-known political figures are named. Semantically, all associations are divided in general cultural, economic and political, such ones that express aesthetic perception of the word-stimulus, as well as those related to travel and leisure. Special attention in the article is given to emotional coloring of reactions (they are divided in positive, negative and neutral). Thus, the material presented in the work reflects, to a certain extent, the perception of the word-stimulus 'Europe' by contemporary student youth.ReferencesГорошко Е. Интегративная модель свободного ассоциативного эксперимента. Харьков: Изд. группа “РА – Каравелла”, 2001.Postolova, I., Tomarieva, N. (2017). Emotional Aspects of Psycholinguistic Experiment with “Europe” as a word-stimulus. Third International Conference Challenges of Psycholinguistics and Psychology of Language and Speech COPAPOLS 2017. Book of Abstracts (77-78). Lutsk: Lesya Ukrainka Eastern European National University.Жаботинская С. Язык как оружие в войне мировоззрений. МАЙДАН- АНТИМАЙДАН: словарь-тезаурус лексических инноваций. Украина, декабрь 2013 – декабрь 2014. Retrieved from: http://uaclip.at.ua/zhabotinskaja-jazyk_kak_oruzhie.pdfReferences (translated and transliterated)Goroshko, E. Integrativnaya model svobodnogo assotsiativnogo eksperimenta [Integrational model of free associative experiment]. Kharkiv: RA–Karavella, 2001.Postolova, I., Tomarieva, N. (2017). Emotional Aspects of Psycholinguistic Experiment with “Europe” as a word-stimulus. Third International Conference Challenges of Psycholinguistics and Psychology of Language and Speech COPAPOLS 2017. Book of Abstracts (77-78). Lutsk: Lesya Ukrainka Eastern European National University.Zhabotinskaya, S. Yazyk kak Oruzhiye v Voyne Mirovozzreniy. MAIDAN-ANTIMAIDAN: Slovar-Tezaurus Leksicheskikh Innovatsiy. Ukraina, dekabr 2013 – dekabr 2014 [Language as a Weapon in the War of Worldviews. MAIDAN- ANTIMAIDAN: Dictionary-Thesaurus of Lexical Innovations. Ukraine, December 2013 – December 2014] Retrieved from: http://uaclip.at.ua/zhabotinskaja-jazyk_kak_oruzhie.pdfДжерелаАсоціативний експеримент. Короткий психологічний словник / за ред. В. Войтко. Київ: Вища школа, 1978.Бутенко Н. Словник асоціативних норм української мови. Львів: Вища школа, 1979.Бутенко Н. Словник асоціативних означень іменників в українській мові. Львів: Вища школа, 1989.Мартінек С. Український асоціативний словник: У 2 т. 2-ге вид. Львів: Паїс, 2008.Славянский ассоциативный словарь: русский, белорусский, болгарский, украинский / под ред. Н. Уфимцевой. М., 2004.Словарь ассоциативных норм русского языка. Прямой / под ред. А. Леонтьева. M., 1973.Черкасова Г. Русский сопоставительный ассоциативный словарь. М.: ИЯ РАН, 2008.SourcesAsotsiativniy eksperiment [Associative experiment]. (1978). Korotkiy Psykhologichnyi Slovnyk [Short Psychological Dictionary]. V. Voytko, Ed. Kyiv: Vyscha Shkola.Butenko, N. (1979). Slovnik Asotsiativnykh Norm Ukrayinskoyi Movy [Associative Dictionary of the Ukrainian language]. Lviv: Vyscha Shkola.Butenko, N. (1989). Slovnyk Asotsiativnykh Oznachen Imennykiv v Ukrayinskiy Movi [Dictionary of Associative Noun Attributes in the Ukrainian Language]. Lviv: Vischa shkola, 1989.Martinek, S. Ukrayinskyi Asotsiativnyi Slovnyk [Ukrainian Associative Dictionary]: in 2 Volumes. 2nd edition. Lviv: Payis, 2008.Slavyanskiy assotsiativnyiy slovar: russkiy, belorusskiy, bolgarskiy, ukrainskiy [Slavonic Associative Dictionary: Russian, Belorussian, Bulgarian and Ukrainian languages]. (2004). N. Ufimtseva, Ed. Moscow.Slovar assotsiativnyih norm russkogo yazyika. Pryamoy [Associative guide of Russian language. Direct] (1973). A. Leontyev, Ed. Moscow.Cherkasova, G. (2008). Russkiy Sopostavitelnyi Assotsiativnyi Slovar [Russian comparative associative dictionary]. Moscow: Institute of Linguistics of the Russian Academy of Sciences.
Keywords: psycholinguistics; associative experiment; word-stimulus 'Europe'; reaction; perception.